Efektifitas Penggunaan Aplikasi Si-Kariwari dalam Pelayanan Administrasi di Distrik Abepura - Maharani Suryaningsih Imanto; Gilbert Aditya; Ardieansyah Ardieansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of information and communication technology has driven public institutions to undertake digital transformation as a strategic measure to establish a modern, efficient, and adaptive form of governance. Digitalization within the bureaucracy, particularly at the sub-district level, has become increasingly urgent in response to the growing complexity of public service demands and citizens’ expectations for fast, accurate, and transparent services. The Abepura District Office, as a local government unit under the City of Jayapura, has adopted various digital information systems to enhance internal administrative functions. One notable system is the SI-KARIWARI application, which serves as a financial management tool used for budget recording, planning, and reporting. This study aims to evaluate the effectiveness of the SI-KARIWARI application in improving administrative service quality at the Abepura District Office. A qualitative descriptive approach was employed, with data collected through direct observation during the academic internship, informal interviews with civil servants, and document reviews of the digital systems used in day-to-day operations. The analysis framework was guided by the principles of Indonesia’s Electronic-Based Government System (SPBE), with evaluation indicators including operational efficiency, data accuracy, budget transparency, and the ease of interdepartmental coordination.